1978
DOI: 10.3109/10826087809039264
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control Research on Alcoholic Populations: A Review. I. Development, Scales, and Treatment

Abstract: Research literature dealing with the relationships of locus of control to alcoholism and the treatment of alcoholism is reviewed. The review includes a discussion of some of the scales used in this research, the relative locus of control of alcoholics compared with controls, the change in locus of control during treatment of alcoholics, and the relationship of locus of control to treatment success. Much of the research is inconclusive. Research on the control orientation of alcoholics compared to controls has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…One of the major reasons why we have war is because people don't take enough interest in politics). Table 32 gives a comparison of the LOC scores in this study with those presented by Rohsenow and O'Leary (1978). Comparisons of externality scores indicates that the alcohol ic and control subsamples measured in this study are higher than those reviewed in locus of control research on alcohol ic populations.…”
Section: Locus Of Controlmentioning
confidence: 96%
See 2 more Smart Citations
“…One of the major reasons why we have war is because people don't take enough interest in politics). Table 32 gives a comparison of the LOC scores in this study with those presented by Rohsenow and O'Leary (1978). Comparisons of externality scores indicates that the alcohol ic and control subsamples measured in this study are higher than those reviewed in locus of control research on alcohol ic populations.…”
Section: Locus Of Controlmentioning
confidence: 96%
“…It is important to discuss this particular measure if for no other reason than it is one of the most widely used assessments in alcoholism research (Rohsenow and O'Leary 1978). This scale has raised interesting questions because it has produced opposite results to those originally hypothesized for alcoholics.…”
Section: Locus Of Control and Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of alcohol consumption is caused by the physical environment and psychological situations of individuals (Rohsenow & O'Leary, 1978). Donovan and O'Leary (1978) indicated that, according to social learning theory, the probability of behavior is an expectancy that reinforcement will follow potential response and that the individual perceives the reinforcement value and the nature of psychological situations in which the behavior is to occur.…”
Section: Introductionmentioning
confidence: 99%
“…In past alcoholism literature, feelings of control, or power have been most often measured using the health locus of control scale [Rohsenow and O'Leary, 1978;Morrison and Schuckit, 1983;Huckstadt, 1987;Dean and Edwards, 1990;Fleming and Barry, 1991;Werner and Broida, 1991;Neff, 1994;Marchiori et al, 1999]. Health locus of control is conceptualized as a personality trait rather than a belief, such as fatalism or perceived personal control.…”
Section: Introductionmentioning
confidence: 99%